1989
DOI: 10.1113/jphysiol.1989.sp017581
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin receptor antagonism by peptidergic and non‐peptidergic agents in rat pancreas.

Abstract: SUMMARY1. Graded doses of bombesin infused I.v. into conscious rats with chronic pancreatic fistulae induced a dose-dependent stimulation of protein secretion, similar to that obtained with caerulein. This stimulation does not appear to be mediated by cholecystokinin (CCK) receptors because peptidergic (CR-1409) and non-peptidergic (L-364 718) CCK antagonists failed to affect protein secretion at a dose range which caused almost complete suppression of caerulein-induced pancreatic secretion.2. Studies in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These hormones do not, however, seem to mediate the trophic action of bombesin on the pancreas because the blockade of specific receptors for gastrin and CCK failed to affect the increase in DNA synthesis by this pep tide. This is in keeping with pervious find ings that bombesin exerts direct action pre dominantly on pancreatic secretion and tis sue growth without mediation of gastrin or CCK [24,37], Bombesin-like immunoreactivity has been found in the brain and in the nerves of the gastrointestinal tract and the pancreas [9,10,38], This widespread distribution of bombe sin suggests that the peptide may play an important role in the control of gastrointesti nal functions. Despite the fact that exoge nous bombesin administered for 48 h was found to stimulate DNA synthesis, the block ade of bombesin receptors by a specific antagonist failed to affect refeeding-induced DNA synthesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These hormones do not, however, seem to mediate the trophic action of bombesin on the pancreas because the blockade of specific receptors for gastrin and CCK failed to affect the increase in DNA synthesis by this pep tide. This is in keeping with pervious find ings that bombesin exerts direct action pre dominantly on pancreatic secretion and tis sue growth without mediation of gastrin or CCK [24,37], Bombesin-like immunoreactivity has been found in the brain and in the nerves of the gastrointestinal tract and the pancreas [9,10,38], This widespread distribution of bombe sin suggests that the peptide may play an important role in the control of gastrointesti nal functions. Despite the fact that exoge nous bombesin administered for 48 h was found to stimulate DNA synthesis, the block ade of bombesin receptors by a specific antagonist failed to affect refeeding-induced DNA synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…CCK is generally recognized as the major hormonal stimulant of pancreatic enzyme secretion and tissue growth [32][33][34][35]. One piece of evidence that endogenous CCK is involved in the stimulation of pancreatic se cretion and tissue growth is derived from the studies with soybean trypsin inhibitor which was reported to increase both these pan creatic functions [36,37], Using the specific CCK receptor antagonist, L-364,718, that eliminates the action of circulating CCK without affecting the release of the hormone, we showed that such CCK antagonism abol ished the enhancement of DNA synthesisinduced cerulein as well as by using soybean trypsin inhibitor (FOY 305) but not penta gastrin or bombesin [37], This study was undertaken to determine the role of CCK in feeding-induced pancreatic growth. As re ported by others [12], we observed that the refeeding with typical rat chow significantly elevated plasma CCK levels and also in creased DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Such infusion of caerulein in chronic pancreatic fistula rats caused a marked increase in protein output from basal secretion of 10 mg/30 minutes to 40 mg/30 minutes in the first hour of infusion followed by a decline in protein output to [15][16][17][18][19][20] mg/30 minutes in the following hours of the experiment. Exogenous platelet activating factor (50 tg/lkg) injected ip produced similar alterations in weight, protein content, blood flow, and histology of the pancreas but.…”
mentioning
confidence: 99%
“…The mediation of CCK in the ca nine pancreatic secretion induced by bombe sin is also supported by the previous finding that bombesin, unlike CCK, is unable to stimulate amylase release from the dispersed canine pancreatic acini [26], It is of interest that in rats, but not in other species, bombe sin stimulates exocrine pancreas mainly by direct action on acinar cells and not through the release of CCK and gastrin or via cholin ergic pathways. This is supported by obser vations showing that the stimulation of pan creatic protein or enzyme secretion induced by bombesin cannot be suppressed by pep tidergic or nonpeptidergic antagonists of CCK receptors either in vivo or in vitro [ 19,27,28], More detailed studies confirmed the presence of specific and separate receptors for CCK and bombesin-like peptides in the rat pancreas [2].…”
Section: Discussionmentioning
confidence: 85%
“…8] and in others such as rats by direct excitation of aci nar cells [19,27], No comparative studies were performed on cats. The physiological significance of GRP, at least in dogs, is uncer tain, because there is little or no change in plasma peptide level under physiological con ditions, such as feeding.…”
Section: Introductionmentioning
confidence: 99%